Digital Organizational Culture - Serpa, Sandro (2022)
Digitalization is unstoppable and takes place in all domains of human life. One of the areas in which this digitalization has profound implications is organizations, understood as coordinated collective units open to the external environment and that are based on and justified by the fulfillment of purposes that would not otherwise be fulfilled, and that have an organizational culture as, generically, forms of thinking, feeling and acting that are characteristics of each specific organization. Through a focused look on contributions to the definition of the concept of digitalization and future challenges, this paper analyzes and discusses the shaping of the digital component in organizational culture, which materializes in a digital organizational culture. To fulfill this aim, a document search of papers was carried out in two comprehensive databases that focus on this topic that served as the basis for our argument. Digital organizational culture, as a product and a process, is shaped by indeterminacy and uncertainty, in an environment permeated by digital technology. However, it is already a reality that new technologies permeate all spheres of organizations and, therefore, organizations need to put in place a well-planned and well-defined strategy for this whole process of digital transition to accomplish this transformation successfully.